Differential recall of derived and inflected word forms in working memory: examining the role of morphological information in simple and complex working memory tasks - Service, Elisabet; Maury, Sini (Frontiers in Human Neuroscience, 2015)
Working memory has been described as an interface between cognition and action, or a system for access to a limited amount of information needed in complex cognition. Access to morphological information is needed for comprehending and producing sentences. The present study probed working memory for morphologically complex word forms in Finnish, a morphologically rich language. We studied monomorphemic (boy), inflected (boy+’s) and derived (boy+hood) words in three tasks. Simple span, immediate serial recall of words, in Experiment 1, is assumed to mainly rely on information in the focus of attention. Sentence span, a dual task combining sentence reading with recall of the last word (Experiment 2) or of a word not included in the sentence (Experiment 3) is assumed to involve establishment of a search set in long-term memory for fast activation into the focus of attention. Recall was best for monomorphemic and worst for inflected word forms with performance on derived words in between. However, there was an interaction between word type and experiment, suggesting that complex span is more sensitive to morphological complexity in derivations than simple span. This was explored in a within-subjects Experiment 4 combining all three tasks. An interaction between morphological complexity and task was replicated. Both inflected and derived forms increased load in working memory. In simple span, recall of inflectional forms resulted in form errors. Complex span tasks were more sensitive to morphological load in derived words, possibly resulting from interference from morphological neighbors in the mental lexicon. The results are best understood as involving competition among inflectional forms when binding words from input into an output structure, and competition from morphological neighbors in secondary memory during cumulative retrieval-encoding cycles. Models of verbal recall need to be able to represent morphological as well as phonological and semantic information